Bkejwanong Dbaajmowinan = Stories of Where the Waters Divide - McGahey, Monty, II (Michigan State University Press, 2021)
'Bkejwanong means "where the waters part," but the waters of St. Clair River are not a point of separation. The same waters that sustain life on and around Bkejwanong--formerly known as Walpole Island, Ontario--flow down into Chippewas of the Thames, the community to which author Monty McGahey II belongs. While there are no living fluent speakers of Anishinaabemowin in this community, McGahey has fostered relationships with fluent speakers from nearby Bkejwanong. Bkejwanong Dbaajmowinan is a collection of stories from these elders, who understand the vital importance of passing on the language to future generations in order to preserve the beloved language and legacy of the community. Like the waters of St. Clair River, the relationships between language speakers and learners have continued to nourish Anishinaabe communities in Bkejwanong and Chippewas of the Thames, particularly in language revitalization. With English translations, this resource is essential for Anishinaabemowin learners, teachers, linguists, and historians.'--Publisher description